Signalling of DNA damage and cytokines across cell barriers exposed to nanoparticles depends on barrier thickness. - Sood, A; Salih, S; Roh, D; Lacharme-Lora, L; Parry, M; Hardiman, B; Keehan, R; Grummer, R; Winterhager, E; Gokhale, P; Andrews, P; Abbott, C; et al. (2011)
The use of nanoparticles in medicine is ever increasing, and it is important to understand their targeted and non-targeted effects. We have previously shown that nanoparticles can cause DNA damage to cells cultured below a cellular barrier without crossing this barrier. Here, we show that this indirect DNA damage depends on the thickness of the cellular barrier, and it is mediated by signalling through gap junction proteins following the generation of mitochondrial free radicals. Indirect damage was seen across both trophoblast and corneal barriers. Signalling, including cytokine release, occurred only across bilayer and multilayer barriers, but not across monolayer barriers. Indirect toxicity was also observed in mice and using ex vivo explants of the human placenta. If the importance of barrier thickness in signalling is a general feature for all types of barriers, our results may offer a principle with which to limit the adverse effects of nanoparticle exposure and offer new therapeutic approaches.